COST-EFFECTIVENESS OF PULSE OXIMETRY SCREENING FOR CRITICAL CONGENITAL HEART DEFECTS IN ONTARIO. (18th May 2018) - Mukerji, Amit; Shafey, Amy; Jain, Amish; Cohen, Eyal; Shah, Prakeshkumar; Shah, Vibhuti; Sander, Beate
Abstract: BACKGROUND: Critical congenital heart defects (CCHDs) are a leading cause of morbidity and mortality in newborns, and late diagnosis is associated with mortality and worse outcomes. Many jurisdictions in the USA and elsewhere have implemented routine pulse oximetry screening (POS) for CCHD, which the Canadian Paediatric Society has recently endorsed. Cost-effective analyses in USA and Europe support this approach, but the geographical setting of Ontario in relation to its vast yet sparsely populated regions presents unique challenges with regard to POS implementation. OBJECTIVES: To estimate the cost-effectiveness of POS for CCHD in the context of its implementation in Ontario, Canada. DESIGN/METHODS: A cost-effectiveness analysis using a Markov model was conducted inputting values derived from an extensive review of literature, and using relevant local databases. The base-case was a 24-hour clinically stable infant born in Ontario. The model employed the healthcare payer (ministry of health) perspective and a life-time horizon. A number of mutually exclusive health states were created, representative of the natural course of CCHDs. The strategies compared were routine pulse oximetry screening versus no screening. Outcome measures, all discounted 1.5%, were quality-adjusted life months (QALMs), lifetime costs, and incremental cost-effectiveness ratios. An a priori threshold of CAD4, 166.67 per QALM (equivalent to CAD50, 000 per quality adjusted life year) was used. Probabilistic sensitivity analysis was conducted using multiple simulations of the model within expected range of variables included in the model. RESULTS: The incremental cost of performing POS was estimated to be 27.27 per individual, with a gain of 0.02455 QALMs (Table 1 ). This yielded an incremental cost-effectiveness ratio (ICER), [Δ Cost / Δ QALMs] of CAD1, 110.79, well below the pre-determined threshold for cost-effectiveness. A probabilistic sensitivity analysis estimated a 93% chance of routine implementation of POS of being cost-effective, with majority of simulated ICERs lying below the threshold of acceptability (Figure 1 ). CONCLUSION: Routine implementation of POS for CCHD is expected to be cost-effective with a high degree of certainty. Further validation of this model may be conducted following implementation to confirm these findings based on local population data.